Keterikatan Emosional Mahasiswa terhadap Idol K-Pop: Kajian Kesejahteraan Psikologis dan Tingkat Kecemasan - Siti Revana; Latifatul Munawaroh; Herlina Pratiwi; Ayu Fitriana; Sabila Jamil, Ayesha (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2026)
The growing popularity of K-Pop among college students has fostered emotional attachments between fans and their idols, potentially impacting individual psychological well-being. This study aims to describe students' emotional attachments to K-Pop idols and their relationship to psychological well-being and anxiety levels. The study employed a descriptive qualitative method, involving 10 student K-Pop fans as respondents. Data were collected through an open-ended questionnaire distributed online and analyzed descriptively. The results indicate that emotional attachments to K-Pop idols tend to have a positive impact on students' psychological well-being. K-Pop idols serve as a source of entertainment, motivation, and emotional support, and help respondents manage the stress and pressures of daily life. Furthermore, involvement in fandom activities increases self-confidence and encourages self-development. The study also found that respondents did not experience excessive anxiety due to emotional attachments to K-Pop idols. These findings imply that emotional attachments to K-Pop idols can be a source of positive psychological support as long as they are within healthy limits and do not interfere with daily activities.